Classification of business processes in an ontology: a case study applied to the Brazilian electricity sector (Advances in Knowledge Representation, 2021)
Organizations in general have experienced countless transformations in their processes imposed by a society that suffers constant mutations, this abstract entity, understood as a macro system involving several processes, understanding the role played in each of them is important in order to optimize their processes with a view to achieving its goals. Ontologies as an artifact of CI., has contributed in numerous domains of knowledge. The elaboration of an ontology with a realistic nature imposes an analysis of the constitution of objects and facts, in order to better classify it into an ontology that has the characteristic of favoring an efficient environment in the management of information. Given this, this study sought to identify how to represent business processes in a domain ontology, seeking to illustrate in a practical way, the study was directed at some processes present in the domain of the electricity sector. The research was classified as qualitative, described and used document analysis as methods. As a result, it was possible to verify how to identify and justify why this classification is used based on the precepts of a high-level ontology, in a preliminary way it was possible to verify the necessary characteristics to carry out the classification of processes in an ontology, building on the understanding of the necessary treatment to be given when these cases occur.